(3OhQ Gd`HQGeL GdJdjaRjhfjI HGdaVGFjGJ GdeUQjI aj JhYjI ChdjGA GdCehQ HGVWQGH GdJhMO dOi GdCWaGd (B/s - (3,Y````dG eMeO ceGd eMeOs; (3UGHQ SdjeGf YSQGfs (2024)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa Ydi GdOhQ GdPj Jbhe Hg GdHQGeL GdJdjaRjhfjI GdebOeI HGdaVGFjGJ GdeUQjI ai JhYjI ChdjGA GdCehQ HGVWQGH GdJhMO dOi GdCWaGd, hGdJYQa Ydi eOj JCKjQ eTGgOI GdJdjaRjhf Ydi CWaGd GdJhMO; hPdc dJSdjW GdVhA Ydi XGgQI (B" (3GVWQGH GdJhMO(B" (3HGYJHGQgG ef Cge GdXhGgQ GdJj JUjH GdYOjO ef GdCWaGd aj Sf eHcQ, HGdEVGaI Edi GdJYQa Ydi eOj GYJeGO ChdjGA GdCehQ Ydi GdHQGeL GdJdjaRjhfjI HGdaVGFjGJ GdeUQjI aj GdMUhd Ydi eYdheGJ Yf GVWQGH GdJhMO(B. (3hGSJNOeJ GdOQGSI GdMGdjI fXQjJj GdJYdb hfehPL GdGSJNOGeGJ hGdJCKjQGJ cEWGQ fXQj dgG, ceG GYJeOJ GdOQGSI Ydi efgL GdeSM HTbjg Gdcej hGdcjaj, hJe Yed GSJeGQI GSJHjGf, LQi edDgG YHQ GdebGHdGJ GdeHGTQI eY ChdjGA CehQ CWaGd GdJhMO, MjK Je GdJWHjb Ydi YjfI YeOjI bhGegG (B(150) (3eaQOI ef ChdjGA CehQ CWaGd GVWQGH GdJhMO, HGdEVGaI Edi GSJNOGe COGI GdebGHdI GdeJYebI MjK Je ELQGA (B26 (3ebGHdI eJYebI eY GdbGFejf HGdGJUGd HGdaVGFjGJ GdeUQjI hGdJdjaRjhf GdeUQj HeGSHjQh, hGdCWHGA hGdCNUGFjjf GdfaSjjf(B. (3hCge eG JhUdJ Edjg GdOQGSI ef fJGFL(B: (3LGA HQfGeL GdSJGJ eGjYQahT jcOHhG aj GdeQJHI GdChdi, HfSHI (B33.3% (3HGYJHGQg ef GdHQGeL GdCcKQ aGFOI hGYJeGkOG Ydjg ChdjGA GdCehQ aj GdMUhd Ydi eYdheGJ Yf GVWQGH GdJhMO(B. (3hJHjf Cf GdZGdHjI GdYXei ef ChdjGA GdCehQ jHMKhf aj GdHQGeL GdJdjaRjhfjI Yf eYdheGJ YedjI hJWHjbjI deYQaI GdJYGed eY Wad GdJhMO HfSHI (B90%. (3hJHjf Cf (B75.3% (3ef ChdjGA GdCehQ jQhf Cf GdaJQI GdeSGFjI ef (B(6-9 (3eSGkAG(B) (3Cge aJQI dHK GdHQGeL GdJdjaRjhfjI defGbTI ehVhYGJ Yf CWaGd Phj GVWQGH GdJhMO(B. (3hGJVM hLhO YdGbI GQJHGWjI Hjf eYOd eTGgOI GdHQGeL GdJdjaRjhfjI HGdaVGFjGJ GdeUQjI heSJhi hYj ChdjGA CehQ HGVWQGH GdJhMO dOi GdCWaGd(B. (3hYOe eYfhjI GdYdGbI GdGQJHGWjI Hjf JGQjN GcJTGa EUGHI GdWad HGVWQGH GdJhMO heSJhi hYj ChdjGA CehQ HGVWQGH GdJhMO dOi GdCWaGd(B. (3hCjkVG hLhO aQhb eYfhjI Hjf ChdjGA GdCehQ YjfI GdOQGSI aj eSJhi hYjge HGVWQGH GdJhMO dOi GdCWaGd, hPdc MSH eJZjQ GdeSJhi GdJYdjej dYGFd GdWad, HjfeG dG JhLO aQhb eYfhjI Hjf ChdjGA GdCehQ YjfI GdOQGSI aj eSJhi hYjge HGVWQGH GdJhMO dOi GdCWaGd, hPdc MSH eJZjQ GdfhY, heMd GdEbGeI, heSJhi GdONd GdTgQj dYGFd GdWads
The current study aimed to identify the role played by television programs presented on Egyptian satellite channels in educating parents about autism disorder in children, and to identify the extent of the impact of watching television on autistic children. This is to shed light on the phenomenon of (3z(Bautism disorder(3y (Bas one of the most important phenomena that affects many children at an early age, in addition to identifying the extent to which parents depend on television programs on Egyptian satellite channels to obtain information about autism disorder. The current study used attachment theory and the uses and effects model as a theoretical framework for it. The study also relied on the survey method, both quantitative and qualitative. A questionnaire form was created, which was filled out through direct interviews with parents of autistic children. It was applied to a purposive sample of (150) individuals from Parents of children with autism disorder, in addition to using an in-depth interview tool, where 26 in-depth interviews were conducted with those responsible for contacting Egyptian satellite channels and Egyptian Maspero TV, as well as doctors and psychologists. The most important findings of the study: The Women Don$1 (Bt Know They Lied program came in first place, with a rate of 33.3%, as it is one of the most useful programs that parents rely on to obtain information about autism disorder. It turns out that the vast majority of parents search television programs for practical and applied information to learn how to deal with an autistic child, at a rate of 90%. It was found that 75.3% of parents believe that the evening period (6-9 p.m.) is the most important period for broadcasting television programs to discuss topics about children with autism disorder. It became clear that there is a correlation between the rate of watching television programs on Egyptian satellite channels and the level of awareness of parents about autism disorder in children. The correlation between the date of discovery of a child with autism disorder and the level of awareness of parents about autism disorder in children is not significant. There are also significant differences between the parents of the study sample in their level of awareness of autism disorder in children, according to the variable of the educational level of the child$1 (Bs family, while there are no significant differences between the parents of the study sample in their level of awareness of autism disorder in children, according to the variable of gender and place of residence , and The monthly income level of the child$1 (Bs breadwinner.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B161-168.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdHQGeL GdJdjaRjhfjIs; (3GdGWaGd GdThGPs; (3GdHQGeL GdJdjaRjhfjI HGdaVGFjGJ GdeUQjI s -- (3GdJhYjIs -- (3ChdjGA GdCehQs